THE NOTION OF SYMPHONY. A LABYRINTH FOR A RESEARCHER? (Mūzikas akadēmijas raksti, 2024)
The image of ancient Greeks’ Fenix proves to be useful to acquaint ourselves with the idea of symphony and partly with its experience nowadays. The word symphony is well-known, but do we know the realm it originated from? The author’s purpose was to make an experimental comparison between the terminology (like the heritage of the past) and more relaxed manifestations of individual Latvian symphonies. Research into etymology and new approach to its inner development is more characteristic of Russian music scientists – such as J. Holopov and T. Scherbo. Unfortunately, musicologists of Latvia are not going into the terminological aspects of the above mention.